Travel Flow: Digital Solutions to Outgrow the Overtourism in Bali - I Made Trisna Semara; A.A. Ayu Arun Suwi Arianty; Moh Agus Sutiarso; Wayan Agung Panca P; Tasya Winston (Centre of Excellence in Tourism Udayana University, 2025)
Bali, as one of Indonesia’s premier tourism destinations, continues to face challenges of overtourism, particularly in popular areas such as Kuta, Ubud, and Sanur. This phenomenon has contributed to environmental degradation, declining visitor satisfaction, and limited benefits for local communities. Addressing these challenges requires innovative approaches that balance tourism growth with sustainability. This study evaluates the potential of TravelFlow, a smart-tourism application designed to manage visitor distribution and mitigate overtourism. Using a qualitative approach, data were collected through observations and in-depth interviews with key stakeholders, complemented by Internal–External Factor Analysis (IFAS–EFAS) and SWOT analysis to assess strategic feasibility. The findings reveal three major insights: first, TravelFlow demonstrates strong potential to redirect tourist flows toward alternative destinations, reducing pressure on overcrowded hotspots; second, successful adoption depends on aligning digital solutions with community participation and ensuring adequate infrastructure readiness; and third, integration with sustainable tourism policies is critical to ensure the application’s long-term effectiveness. The study highlights that application-based solutions such as TravelFlow can serve as practical tools to foster more balanced tourism development in Bali. By redistributing visitor flows, enhancing environmental responsibility, and promoting community involvement, smart-tourism initiatives hold promise in mitigating the negative impacts of overtourism while supporting a more sustainable and inclusive tourism future.